Creative Thinking Problems of Junior High School Students in Solving Geometry Problems of Transformation Class IX - Fitriyani, Fitriyani; Kusno, Kusno (Proceedings Series on Social Sciences & Humanities, 2025)
Creative thinking skills are important in learning mathematics. However, many students have difficulty thinking creatively, especially in the subject of transformation geometry. Initial observations at Putra Harapan Boarding School Junior High School Purwokerto show that most grade IX students have difficulty in showing aspects of fluency, flexibility, originality, and elaboration when solving transformation geometry problems. This study aims to analyze creative thinking problems in grade IX students in solving transformation geometry problems. The research method used was qualitative descriptive with the research subjects of three students selected based on the category of high, medium, and low initial ability with purposive sampling techniques. The research instruments were in the form of descriptive tests and semi-structured interviews. The data analysis technique uses triangulation. The results showed that students with high ability categories showed good creative performance formally, but experienced difficulties in the depth of conceptual thinking and originality of ideas. Students with moderate abilities have the potential for fluency and originality, but experience challenges in flexibility and elaboration of thinking. Students with low ability showed problems on all indicators of creative thinking. This study recommends the use of deep learning approaches to improve students' creative thinking skills.